Centralização cerebral materna na doença hipertensiva específica da gestação - Franco, Glaucimeire Marquez (2015)
Introduction: Preeclampsia and eclampsia are important causes of maternal and perinatal morbidity and mortality worldwide Objectives: To evaluate the maternal brain centralization in pregnant women with specific gestational hypertension. Produce a systematic review article on the ophthalmic artery Doppler and uterine artery and the flow-mediated dilation. Develop an original article in order to assess the possible occurrence of maternal brain centralization in pregnant women with specific gestational hypertension. Establish normal values of the ratio of uterine artery to the ophthalmic artery (mean and standard deviation). Compare the ratio of uterine with the ophthalmic artery in normal and pathological group. Set the cut-off point, using the ROC curve for specific diagnosis of patients with hypertensive disease of pregnancy. Methods: A systematic literature review involved 260 indexed articles from Medline via PubMed and Virtual Health Library (VHL), published between 1989 and 2014. For the original article, we performed a case-control study of 178 pregnant women divided into two groups: a control group of normal patients (PN), a total of 83 normotensive pregnant women; and one case group of 95 patients with specific gestational hypertension. The analyzed parameters which formed part of the variables studied were: systolic velocity (VS), diastolic velocity (RV), the resistance index, systole-diastole relationship. In addition to these variables were also studied epidemiological variables of pregnancy, parity, abortion, weight, height, BMI, maternal age, gestational age. Results: Through the search strategy, were located 260 articles, of which 33 articles were eligible, with fifteen articles on the ophthalmic artery, eight articles on the brachial artery and eight articles on uterine artery. A total of 178 patients took part in study. The average age of normal pregnant women group of patients was 29.8 ± 4.7 and patients with specific gestational hypertension, of 26.14 ± 6.17. The mean gestational age of normal pregnant patients was 34.3 ± 3.5 weeks and the patients with specific gestational hypertension, of 32.40 ± 3.37. The mean body mass index (BMI) of healthy patients was 26.8 ± 5.6 and patients with specific gestational hypertension, of 30.55 ± 5.12. A normality curve systole-diastole compared with the respective cutoff was performed. A ROC curve was developed, with the cutoff point, considering the systolic velocity, diastolic velocity, systolic-diastolic ratio and the resistance index of the ophthalmic artery, respectively. Conclusion: The Doppler uterine artery and ophthalmic artery flow-mediated dilatation can be useful to identify patients at risk for allowing the monitoring of disease progression and perform effective interventions. It is observed that the possibility of maternal centralization in high-risk pregnancy as the PE is real, whereas in the average normal values and the standard deviation of the Doppler AU / AO-systole-diastole ratio were 0.43 ± 0 16. The cutoff point more sensitive, verified by the ROC curve, which defines maternal brain centralization in patients with hypertensive disorders of pregnancy, is 0.57 for the S / D for UD / AO, with 78% sensitivity and 13 % false positive and 77% specificity.